Pediatric surgery in Brazil: Bittersweet - Lisieux Eyer de Jesus; Amanda Guerra Rosina; Beatriz Calsolari Ranha; Maria da Conceição Mendonça de Campos (Elsevier, 2023)
Introduction: Brazil is a low-medium income country with a big territory, characterized by inequalities in population distribution and social development towards the country, affecting the distribution of physicians and medical technology resources. Circa 80% of the population depends on the National Health System (SUS), which is the main employer for physicians. This study aims to describe working conditions, quality of life and professional expectations of BPS. Methods: Electronic survey with Brazilian pediatric surgeons. Results: Females predominate in the younger and males in the older age groups. Most BPS are married, with a minority being single (n= 38, 10.86%) or divorced (n = 31, 8.86%) and most have children. For a quarter of BPS the profession/specialty influenced their decisions concerning family planning. Multiple jobs are common, including BPS that declare themselves half-retired. The geographic distribution of pediatric surgeons is unequal. Only a quarter of BPS work in the mid-center, northern and northern-eastern regions, where almost half of the country population live. Medical technology is inadequately distributed. The main income for most BPS comes from SUS. Most BPS were trained in fellowships. Most BPS are satisfied with their specialty choice (n = 255, 72.86%), but many judge the future of Pediatric surgery in Brazil as unfavorable (n = 130, 37.14%). Childless females represent 29.78%, versus 6.4% of the males (p < 0.00001) and more females than males restrict their families to one child (p = 0.00001). 42.7% of the women (n = 76) admitted that work has deeply influenced family planning. Age of the first child tended to be higher for women. Discussion: Research about the professional realities and perspectives is important to plan the future of the specialty. Professional expectations and real-life problems cannot be directly transferred between different economic and social environments. Our data suggest that females will largely predominate among pediatric surgeons in Brazil in the near future. Multiple jobs and big workloads are related to attrition, burn out, disillusionment, and lower productivity. The relative low number of BPS that are satisfied with their professional choices, and, especially, the high proportion of BPS that predict an unfavorable future for Pediatric Surgery in Brazil are worrying, especially as disillusionment predominates among the younger BPS. The main complaints registered in this research were related to low wages, low prestige of the specialty, and unrestrained competition among colleagues, that may be obviously related.